Groundwater Exploration in Aaba Residential Area of Akure, Nigeria - Adagunodo, Theophilus A.; Akinloye, Margaret K.; Sunmonu, Lukman A.; Aizebeokhai, Ahzegbobor P.; Oyeyemi, Kehinde D.; Abodunrin, Felicia O. (Frontiers in Earth Science, 2018)
Groundwater plays a fundamental role in human life. Despite its indispensable characteristics, it is unfortunate that groundwater is often associated with low yield. The expanding demand for water and the cost involved in drilling boreholes therefore require the application and the proper use of groundwater investigation techniques to locate high yielding aquifers. A geophysical investigation involving an electrical resistivity method using a Schlumberger electrode array was conducted around Aaba residential area, a basement terrain of southwestern Nigeria. Sixteen Vertical Electrical Sounding (VES) stations were applied across the study area using a maximum current electrode separation of 100 m. The geoelectrical imaging from this study revealed that the lithologies are divided into topsoil, lateritic soil, Sandy clay/ clayey sand/ clay/ weathered rock and the bedrock. Subsurface geoelectrical maps (overburden thickness, weathered layer isothickness, weathered layer isoresistivity, bedrock relief, bedrock resistivity and correlations from geoelectric sections) were used to generate information about the groundwater potential of the study area. It was inferred that the eastern (VESs 1, 2, 8, 10 and 11) and the southwestern (VESs 13 and 14) regions are associated with high groundwater yield. Boreholes can be drilled to an average depth of 22.0 m (72.6 ft) on these axes. The groundwater potential of the northern (VES 5), central (VES 9), and southern (VES 12) parts of the study area were inferred to be of medium potential. The borehole drilling along these axes can be extended to the depth of 30.0 m (99.0 ft), with medium groundwater yield. However, the northeastern (VES 3 and VES 4) and the western (VESs 6, 7, 15, and 16) zones are characterized by low groundwater potential. This present study has been able to detect the drillable zones and depths for optimum groundwater yield in a crystalline terrain of Aaba residential area, Akure using VES. The resistivity sounding is efficient in characterization of aquifers for groundwater exploration.